United States and District of Columbia government collection
Essays on various aspects of government and the election of officials and abstracts of government reports.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States -- Politics and government -- 19th century; Washington (D.C.) -- Politics and government -- 19th century